Analysis of differential expression of genes induced by ethephon in elongating internodes of maize plants - Xiaoyi WEI,Weiqiang ZHANG,Qian ZHANG,Pei SUN,Zhaohu LI,Mingcai ZHANG,Jianmin LI,Liusheng DUAN (Frontiers of Agricultural Science and Engineering, 2016)
Plant growth regulators (PGRs) are commonly used in cereal cropping systems to restrict plant height and control lodging. Ethephon has been reported to shorten internodes and increase grain yield of maize. To analyze the transcriptomic profiles of maize internode elongation following ethephon treatment, differentially expressed genes were compared between the treatment and control samples of inbred line Zong 31 using the Affymetrix Maize Genome Array. According to the microarray data, 326 probe sets showed significant change in expression. Further research revealed that the most remarkable effects of ethephon on maize internodes elongation occurred during a 48 h period, when 89 differentially expressed genes were detected. There were dramatic change in transcript levels at 24 h and six Auxin transport genes and four gibberellin biosynthesis pathway genes were differentially expressed in Zong 31 in response to ethephon treatment. In summary, we showed that gaseous ethylene release is involved in internode meristem cell elongation through the regulation of plant hormone signaling in maize. This work provides a platform for studies in which candidate genes will be functionally tested for involvement in internode elongation.